Biomedical applications of aluminium oxide nanoparticles. (1st September 2018) - Hassanpour, Peyman; Panahi, Yunes; Ebrahimi‐Kalan, Abbas; Akbarzadeh, Abolfazl; Davaran, Soodabeh; Nasibova, Aygun N.; Khalilov, Rovshan; Kavetskyy, Taras
Abstract : Aluminium oxide (Al2 O3 ) nanoparticles (AlNPs) are class of metal oxide nanoparticles that have diverse biomedical applications owing to their exceptional physicochemical and structural features such as resistance towards wear, chemicals, mechanical stresses as well as their favourable optical properties and a porous vast surface area. Other reasons for widespread applications of AlNPs are their low cost of preparation and easy handling. Therefore, owing to the economic importance, the recent achievements and possible health risks associated with the biomedical applications of AlNPs are overviewed in this work.